Nineteenth Century Local Governance in Ottoman Bulgaria - Saracoglu, M. Safa.
1 online resource (215 pages)
Keywords: This book provides a detailed exploration of the way in which administrative and judicial offices and practices provided an essential space for politics in 19th-century Bulgaria, securing local inhabitants' participation with Ottoman imperial governance.